A STUDY ON THE CBCT EVALUATION OF THE CONFIGURATION OF THE ENDODONTIC SYSTEM AT THE LEVEL OF THE UPPER FIRST MOLAR - Adela Cenușoiu; Bugălă Narcis-Mihăiță; Lelia Gheorghiță; Oana Andreea Diaconu; Monica Scrieciu; Cristian Petcu; Sanda Mihaela Popescu; Adina Turcu; Ruxandra Voinea Georgescu; Mihaela Jana Țuculină (Romanian Society of Oral Rehabilitation, 2021)
The endodontic system is complex and has many anatomical variations within different population groups. The success of any endodontic treatment depends on the comprehensive knowledge of the internal morphology of the canals, the achievement of an access cavity and a correct chemo-mechanical treatment, as well as the quality of the canal obturation. Lack of knowledge in this regard and omission of a root canal are among the most common causes of failure of endodontic treatments. Most previous studies on the first molars of the jaws have shown that they have three roots and four channels, because an additional channel is often found at the mesio-vestibular root. Other anatomical variations, such as an additional C-shaped canal, have also been reported in the disto-vestibular and palatal roots. Thus, due to the fact that they have a more complex anatomy compared to other teeth, the 1 maxillary molars have the highest rate of endodontic failure. Recently, CBCT has been used to explore the three-dimensional details of the root canal before endodontic treatment. The aim of this study is to highlight the importance of in-depth knowledge of the root canal morphology of the first permanent maxillary molar.